Unpublished economic texts from Tell Harmal - Albaldawi, Shaymaa; Hussien, Laith (Al-Adab Journal, 2025)
Cuneiform texts played an important role in ancient Iraq. Through them, we were able to know the first written language in the world, which led us to the secrets and treasures of cuneiform writing. We were also able to know the various sciences and knowledge that they reached. Economic texts are considered one of the most important types of cuneiform texts, as these texts contain Various contracts and daily transactions such as buying, selling, leasing, mortgage, guarantee, distribution, etc...., the study of which is of great importance because it fills a large gap in our knowledge about the nature of the economic situation in those eras and how daily life was going in that society. The texts studied in this research included texts Especially for distributing barley to a group of people. They also all have in common the fact that king (Ibalbel II 1785-1773 BC), who ruled in the city of Tel Harmal (Babylonian ancient Shadboum). His rule lasted 19 years, and his period of rule is considered one of the most important. During the periods in the Kingdom of Eshnunna, the kingdom reached the height of its greatness, and his interest was not limited to one aspect only. He was interested in building and bringing statues, as well as the military aspect.